SINESTESIA PADA KUMPULAN PUISI ROMANTIS KARYA SAPARDI DJOKO DAMONO: KAJIAN SEMANTIK - Robby Yudhi Nurhana; Wahyu Fifit Setyaningrum; Yuentie Sova Puspidalia (Universitas Hamzanwadi, 2024)
This paper is to describe the use of synesthesia in romantic poems by Sapardi Djoko Damono. The data source is a collection of romantic poems by Sapardi Djoko Damono containing synesthesia, namely Hujan Bulan Juni, Kuhentikan Hujan, Sajak Putih, Gerimis Jatuh, Hujan dalam Komposisi 1, and Hujan dalam Komposisi 2. Given that this research uses a qualitative descriptive approach, the data used is in the form of exposure to poetry texts in a collection of romantic poems by Sapardi Djoko Domono containing synesthesia elements. To find the synesthesia in question, an analysis with read and write technique is used. Through analysis based on Leech's theory of meaning types. The results showed that synesthesia is found in 6 poems out of 22 romantic poetry collections by Sapardi Djoko Damono. In the poem Hujan Bulan Juni there is one synesthesia, namely vision-feeling (heart). Kuhentikan Hujan, there are two synesthesia, namely vision-feeling (heart) and vision-touching. Sajak Putih, there is one synesthesia, namely hearing-sight. Gerimis Jatuh, there are two synesthesia: hearing-sensing and seeing-sensing. Hujan dalam Komposisi 1, there are two synesthesia: hearing-sensing and smell-sensing. Hujan dalam Komposisi 2, there is one synesthesia, namely hearing-sight. Synesthesia can be used effectively in enriching the reader's experience, creating a deeper and emotional picture because synesthesia is a literary technique that combines two or more senses to create a more complex and rich picture.